Recent Trends in Modelling of Environmental Contaminants - Sengupta, Debashish (Springer India : Imprint: Springer, 2014)
The book deals primarily with the aspects like energy resources and its proper utilization, disposal of various forms of wastes and its effects, and effects of major catastrophic events like nuclear disasters, global warming, etc. It also deals with the choice of suitable disposal sites for solid and hazardous waste, which is growing at an extremely rapid pace due to rapid industrialization, population growth (primarily in countries like India and China) and urbanization. In addition groundwater contamination due to various causes and its effect on the food chain is also amply discussed. The book is specifically aimed with the state-of-art information regarding research and development in these areas of study, coupled to extensive modelling and case based results obtained, both from India as well as other countries. The book is extremely instructive for the students, research workers, scientists, faculty members in Applied Physics, Solid Earth Geophysics, Radiometric Methods and Exploration, Ground Water Geochemistry, Mathematical Modeling Techniques in Earth Sciences, Near Surface Geophysics and Earth and Environmental Sciences.